She should have died hereafter? When is death caused in law by breach of duty?. (September 2015) - Feeny, Charles; Samuel, Ana; Austin, Charles
The article examines the law surrounding causation in situations when a death could be said to have been accelerated with particular reference to the case of Davies v Countess of Chester Hospital [2014] EWHC 4294 (QB). In doing so, the authors will argue that there are two options available to the courts, one that is an arbitrary time limit and the second which focuses on materiality.